SOLUTIONS FOR LATGALIAN ORTHOGRAPHY PROBLEMS IN THE PRESS IN THE FIRST HALF OF THE 20th CENTURY - Bernāne, Līga (Via Latgalica, 2008)
As soon as the ban on printing was abolished, one particular solution for the question of Latgalian orthography was found. However, it could not satisfy all language users, since it was too complicated and did not solve all orthographic problems. Teachers were not satisfied by the established orthographic rules either, because the reproduction of phonetic forms did not correspond to the forms as used among the people. However, although historic events were dramatic and tough in the first half of the 20th century (war, change of government, foundation and consolidation of an independent state), the work of linguists was not suspended – newspapers featured publications about language problems, orthography conferences were organized, and books on grammar were published. The amount of publications during that time was quite impressive. Therefore, their review is divided into the following periods: 1. From 1908–1918 only two Latgalian printed publications, „Drywa” and „Jaunas Zinias”, existed on a long-term basis. These paid a great deal of attention to the integrity of the language and problems of orthography, and the authors of the articles were concerned with the „pollution” of the language by germanisms and baltisms. There are only a few publications, for example, an article by Ontons Skrinda called „Woludas waicojumâ”(literally - „On the Issue of Language”, „Drywa”, 21/1913), which raises concrete questions about spelling and orthography. 2. During the time from 1920, when the political situation in the new Latvian state in the post-war period became stable, until the 1923 orthography conference, discussions of problems of language and orthography became even more ardent, articles became more thorough, and there were less pathetic appeals. The paper reviews articles from the magazine „Zīdūnis”, and the newspapers „Latgolas Wōrds” and „Latgalītis”.. Authors of the most important publications of that period are Francis Kemps, Francis Trasuns, as well as Piters Strods, who became the most active and progressive promoter and reviewer of the discussion around orthography problems. 3. From 1923 until 1927 an orthography committee was appointed by the Ministry of Education. Its decisions were binding for all the users up until the end of the 20th century. During that period of time a lot of periodicals were published in Latgalian. Articles on the problems of language and orthography, however, can mainly be found in the newspaper „Latgolas Vōrds”, as well as in the magazines „Latgolas Škola” and „Zīdūnis”. The author of the most serious and thorough articles is P. Strods, who at that time became the main promoter of the solution of the orthographic problems. Unfortunately, there are plenty of publications where the authors’ personal ambitions are more dominant than the questions regarding the problems of orthography. All in all, it can be concluded that all the publications of the first half of the 20th century can be divided into two groups: 1. those which deal with general questions of the existence of the Latgalian language existence and its development, but do not discuss particular orthography problems, and 2. those in which the authors refer to the solution of particular orthography problems and offer concrete suggestions.